Structural Characterization of Al2O3 and CeO2 Supported Ni, Co Loaded Ceramic Monolithic Catalysts - Guldal, N. O.; Baykara, S. Z. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
This paper discusses structural characterizations of monolithic catalysts prepared by incorporating Ni and Co supported over a porous alumina and ceria layer by using respective nitrates and H2PtCl6 as precursors. Monolithic catalysts were synthesized by dip-coating of 400 cpsi cordierite ceramic monolithic pieces cut in 20 x 13 mm(2) (L x D) into appropriate solutions of metals, followed by calcination in air at 800 degrees C for 4 h. Phases of catalysts were characterized with X-ray diffraction. Morphological analysis and elemental composition were determined by scanning electron microscope and energy dispersive spectroscopy. The specific surface area analysis have been studied using the Brunauer-Emmett-Teller method. Metal contents were determined by inductively coupled plasma optical emission spectrometry.
Keywords: PARTIAL OXIDATION; HYDROGEN-PRODUCTION; SYNTHESIS GAS; METHANE; ETHANOL; Physics